The Dangers of Bad History as a Source of Liberal Bias: Comment on Winegard et al. (2023) - Ferguson, Christopher J. (Journal of Open Inquiry in the Behavioral Sciences, 2025)
Many social science researchers are liberals and progressives. Many published research studies also happen to support liberal and progressive narratives. This is even true for published research articles which might be fairly interpreted as insulting of conservatives such as referring to them as racist or unintelligent. Is this a coincidence? In a series of impressive studies, Winegard et al. (2023) demonstrate that political bias influences liberals’ perceptions and that, in the quest for finding equality, liberals assign greater moral worth to minority groups than majority. These findings have important implications for recent revisionist history approaches within education, and potential misinformation spread among youth in schools.